2019
DOI: 10.1101/cshperspect.a035071
|View full text |Cite
|
Sign up to set email alerts
|

NAADP Receptors

Abstract: Of the established Ca2+-mobilizing messengers, NAADP is arguably the most tantalizing. It is the most potent, often efficacious at low nanomolar concentrations, and its receptors undergo dramatic desensitization. Recent studies have identified a new class of calcium-release channel, the two-pore channels (TPCs), as the likely targets for NAADP regulation, even though the effect may be indirect. These channels localized at endolysosomes, where they mediate local Ca2+ release, and have highlighted a new role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 193 publications
(280 reference statements)
0
40
0
Order By: Relevance
“…TPCs are gated by multiple agonists, including nicotinic acid adenine dinucleotide phosphate (NAADP), sphingosine, and the EL phospholipid, phosphatidylinositol 3,5-bisphosphate (Galione 2019). TPCs-mediated Ca 2+ release recruits EL-located Ca 2+sensitive decoders, including calmodulin, synaptotagmin VII, and Arf6 (Faris et al 2018), to regulate vesicular fusion and trafficking (Galione 2019). A screening campaign aiming at repurposing FDA-approved drugs as novel antiviral compounds recently revealed that classical Ca 2+ antagonists blocked Ebola virus and MERS-CoV infections in vitro (Sakurai et al 2015;Gunaratne et al 2018a, b).…”
Section: Repurposing Of Clinically Available Antivirals To Treat Covimentioning
confidence: 99%
“…TPCs are gated by multiple agonists, including nicotinic acid adenine dinucleotide phosphate (NAADP), sphingosine, and the EL phospholipid, phosphatidylinositol 3,5-bisphosphate (Galione 2019). TPCs-mediated Ca 2+ release recruits EL-located Ca 2+sensitive decoders, including calmodulin, synaptotagmin VII, and Arf6 (Faris et al 2018), to regulate vesicular fusion and trafficking (Galione 2019). A screening campaign aiming at repurposing FDA-approved drugs as novel antiviral compounds recently revealed that classical Ca 2+ antagonists blocked Ebola virus and MERS-CoV infections in vitro (Sakurai et al 2015;Gunaratne et al 2018a, b).…”
Section: Repurposing Of Clinically Available Antivirals To Treat Covimentioning
confidence: 99%
“…This issue must be studied further. Similarly, it is unclear which ion channel was responsible for Ca 2+ release, as inside the lysosomal membrane, there are several calcium channels that serve as NAADP receptors, including the two pore channels 1 and 2 (TPC1, 2) with high affinity for NAADP, and transient receptor potential melastatin 2 (TRPM2) with low affinity for NAADP [43]. Which of these channels are involved in NAADP-induced Ca 2+ release has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For some time, studies on the role of protons in cellular processes have taken into consideration the relationship between pH and calcium and its effects, in particular in relation to cellular channels and organelles. Protons modulate the action of various types of channel, including voltage-gated proton channels [DeCoursey 2018] which extrude protons, the Orai/STIM, transient receptor potential (TRP) channels [Yu 2018, Vangeel 2019, and two pore channels (TPC) [Kintzer 2018, Galione 2019] which foster Ca 2+ influx via store-operated calcium entry (SOCE). Sarco-endoplasmic reticulum Ca 2+ -ATPase pump (SERCA) and the plasma membrane Ca 2+ -ATPase pump (PMCA) remove excess Ca 2+ from the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no study attributes a triggering role to protons or makes an in-depth biochemical investigation of the interdependence mechanism between the H + and Ca 2+ ions. Nonetheless, significant progress has been made over the past 40 years or so: several fundamental second messengers and pathways for calcium signaling have been identified [Pozzan 1994, Clapham 2007, Berridge 2012, Balla 2013, Carafoli 2016, Galione 2019, and the understanding of specific receptors [Rossi 2018 and channels [Kozak andPutney 2017, Galione 2019] has improved. Experimental methods, particularly calcium imaging techniques, have been developed [Depaoli 2019, Siciliano 2019.…”
Section: Introductionmentioning
confidence: 99%